#TITLE_ALTERNATIVE# - PRIBADI SETYO, ANSHARY
Gravity method is one of the geophysical methods that can be used to estimate subsurface condition of CO2 sequestration area. This study focuses on the estimation of the gravity response at CO2 sequestration area by creating a synthetic model. A synthetic model has been created using reference data for brine formation and coal seams. Density of CO2 is unknown, so it needs to be calculated first. Furthermore, a simple simulation of CO2 injection to geological fomation has been done to predict the value of anomaly gravity response changes in the period of time. The results showed the relationship between CO2 saturation and gravity response. The higher CO2 saturation in sequestration area, then the gravity response changes will be more negative. Beside that, reservoir depth and thickness can also affect the gravity response changes. For practical considerations, the gravity response changes for a brine formation model with 10% saturation of CO2 will be detected in the field at least at a depth of 700 m and a thickness of 25 m. Whereas for a coal seams model with 10% saturation of CO2, the gravity response changes can still be detected at a depth of 400 m and a thickness of 6 m. Meanwhile, the results of the simulation showed the linear relationship between gravity response changes and injected CO2 mass. Each injection of 1 million tons of CO2 will produce changes in gravity response at the rate of -6 ?Gal assuming there is no leakage of CO2.